COSO FRAMEWORK SEBAGAI BASIS PENILAIAN EFEKTIFITAS PENGENDALIAN INTERNAL PENERIMAAN KAS (STUDI KASUS PT LEP) - Alfonsa Dian Sumarna; Nadya Fortuna Novitasari (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2022)
The important activity within a company that should be controlled in order to help companies obtain the goal are financial activity. To maximize this activity need proper internal controls, ranging from the function of cash receipts, account receiveble, sales and etc. Cash is the most liquid of assets and is susceptible to loss if not properly controlled. Therefore, it is extremely important to all department which is handling cash to implement and adhere to strong internal controls. All staff who collecting cash should ensure proper controls are in place to safeguard collections until deposit. This descriptive qualitative research use case study with the object is PT LEP. This research uses primary and secondary data which is collected by literature study, observation, interview, and questionaire. For ensure validity and reliability data, we run triangular test (source and technique). This research use COSO framework as basis to evaluate effectiveness of internal control in cash receipts. This research found that there are several weaknesses in each component of internal control that need to be concerned to make the implementation internal control better in the future. In the control environtment component, indicators which are need to be improved are philosophy and style management and also authority and responsibility. In the risk assesment component is risk estimation. In the information and communication component are the detailed and timely information. In the control activities component are related to management performance, information and segregation of duties. And for the monitoring component is management’s periodicity and continous monitoring.